2021
DOI: 10.1155/2021/9929470
|View full text |Cite
|
Sign up to set email alerts
|

Research on Simplified Calculation Method of Coupled Vibration of Vehicle‐Bridge System

Abstract: A modified moving loads’ model is proposed for the vehicle-bridge coupling vibration simulation. Taking the vehicle-bridge interaction model (VBI) as the reference, the accuracy and applicability of the three calculation models, namely, moving loads’ model, moving mass model, and spring-damper-mass model, are compared using the frequently-used railway simply-supported beam with a span of 32 meters as the research object. Influencing factors such as vehicle speed, mass ratio of vehicle and beam, and primary spr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Based on the plate and shell theory, Prakash and Barik [4] analyzed the dynamic response of the bridge deck when the vehicle moved at a constant velocity and obtained the center de ection of the bridge deck before and after the reinforcement with sti ening and found that the I-shaped reinforcement contributed more to the strength of the bridge deck (Cheng et al [5]).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the plate and shell theory, Prakash and Barik [4] analyzed the dynamic response of the bridge deck when the vehicle moved at a constant velocity and obtained the center de ection of the bridge deck before and after the reinforcement with sti ening and found that the I-shaped reinforcement contributed more to the strength of the bridge deck (Cheng et al [5]).…”
Section: Introductionmentioning
confidence: 99%